18. Evaluation of acute and subchronic toxicity of “Huyet Phu Truc U Hoan” in experimental animals - Thai, Dang Cong; Nam, Trinh Hoai; Hien, Nguyen Minh; Hien, Dang Thi Thu (Tạp chí Nghiên cứu Y học, 2024)
This research was carried out to evaluate the acute and sub-chronic toxicity of ‘‘Huyet phu truc u hoan’’ (HPTUH) in experimental animals. The acute toxicity was defined on Swiss mice by the Litchfield – Wilcoxon’s method and the sub-chronic toxicity on Wistar rat’s hematopoietic function, liver, and kidney functions according to the World Health Organization Guidance. As a result, with doses from 10g/kg to 50g/kg, LD50 of HPTUH was not determined. With the doses from 2.38g/kg to 7.14g/kg per day on Wistar rat for 8 consecutive weeks, haematological parameters, ALT, AST, urea and creatinine levels were unaffected. In addition, the HPTUH did not produce any toxic effect in the animals’s liver and kidney in the treated animals compared to the control.